POETA DE PUDRICIÓN: LA LÍRICA MACABRA DE ARMANDO URIBE ARCE. - Mahop, Romuald-Achille Mahop-Ma (Revista Chilena de Literatura, 2025)
An essential part of the lyrical work of the Chilean Armando Uribe Arce is marked by ontological meditation, very often articulated around a kind of lyrical phenomenology of death. The present work analyses the poetic figuration of the dead body, the primacy of an eminently macabre lyrical discourse, enunciated in the first person, the expressive resources involved in such a process and its literary and philosophical implications.